Whole‐exome sequencing reveals critical genes underlying metastasis in oesophageal squamous cell carcinoma. Issue 4 (12th July 2017) - Dai, Wei; Ko, Josephine Mun Yee; Choi, Sheyne Sta Ana; Yu, Zhouyou; Ning, Luwen; Zheng, Hong; Gopalan, Vinod; Chan, Kin Tak; Lee, Nikki Pui‐Yue; Chan, Kwok Wah; Law, Simon Ying‐Kit; Lam, Alfred King‐Yin; et al.
Abstract: Oesophageal squamous cell carcinoma (ESCC) is one of the most lethal cancers, owing to a high frequency of metastasis. However, little is known about the genomic landscape of metastatic ESCC. To identify the genetic alterations that underlie ESCC metastasis, whole‐exome sequencing was performed for 41 primary tumours and 15 lymph nodes (LNs) with metastatic ESCCs. Eleven cases included matched primary tumours, synchronous LN metastases, and non‐neoplastic mucosa. Approximately 50–76% of the mutations identified in primary tumours appeared in the synchronous LN metastases. Metastatic ESCCs harbour frequent mutations of TP53, KMT2D, ZNF750, and IRF5 . Importantly, ZNF750 was recurrently mutated in metastatic ESCC. Combined analysis from current and previous genomic ESCC studies indicated more frequent ZNF750 mutation in diagnosed cases with LN metastasis than in those without metastasis (14% versus 3.4%, n = 629, P = 1.78 × 10 –5 ). The Cancer Genome Atlas data further showed that ZNF750 genetic alterations were associated with early disease relapse. Previous ESCC studies have demonstrated that ZNF750 knockdown strongly promotes proliferation, migration, and invasion. Collectively, these results suggest a role for ZNF750 as a metastasis suppressor. TP53 is highly mutated in ESCC, and missense mutations are associated with poor overall survival, independently of pathological stage, suggesting that these missense mutations have important functional impacts on tumour progression, and are thus likely to be gain‐of‐function (GOF) mutations. Additionally, mutations of epigenetic regulators, including KMT2D, TET2, and KAT2A, and chromosomal 6p22 and 11q23 deletions of histone variants, which are important for nucleosome assembly, were detected in 80% of LN metastases. Our study highlights the important role of critical genetic events including ZNF750 mutations, TP53 putative GOF mutations and nucleosome disorganization caused by genetic lesions seen with ESCC metastasis. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.